Constructing the boundary texture of Iranian urban rivers, case study (Shirin Rudi Sari River) - Noruzi, Somayeh; Samadai, Shahrbanoo; Samadai, Mahdi (Innovaciencia, 2019)
Architecture has long been seeking solutions for human well-being and comfort. In this regard, the existence of service spaces, welfarethat both needs both indigenous people and non-native tourists, seems necessary. The development and management of urbanrivers can be one of the choices that, in addition to preserving national resources and ecosystems, have an increasing role to play inimproving the quality of the environment within the boundaries of the city’s rivers. This topic focuses on water conservation and howit can be exploited, and how to use urban rivers and planning to achieve social, economic and environmental achievements along thecity’s riverside streams. The main problem is that in most cities, the boundaries of urban rivers are not regulated and the land abandonedaround rivers. In the meantime, creating a calm environment away from environmental pollution and visual contamination is one ofthe major problems of modern cities, as well as providing suitable facilities for users to benefit from the beautiful scenery of the rivercan be a good solution for this important Be. This research is to study the case study of Shirin Roud River to the Shahid RajaieDam in Sari to study more accurately the environmental, social and economic challenges of urban rivers and provide appropriatesolutions in this regard. In this study, both studies Library and field observations and setting up a questionnaire for access to theoreticalfoundations of design.
Keywords: Architecture, Water Reservoir, Urban Rivers, Shirin Rood